Treatise on process metallurgy. - Seetharaman, Seshadri; McLean, Alexander; Guthrie, Roderick I. L.; Sridhar, Seetharaman (Elsevier, 2014)
This book provides academics with the fundamentals of the manufacturing of metallic materials, from raw materials into finished parts or products. This volume in particular encompasses ferrous processing, non-ferrous processing, and refractory, reactive and aquaeous processing of metals.